Traffic planning of backbone link of quantum secure communication network - Lei YUAN; Meisheng ZHAO (Dianxin kexue)
Quantum secure communication network is a new kind of security network.It is a new problem that how to improve the bandwidth utilization ratio of the backbone link of quantum secure communication network and the network performance-price ratio by reasonable traffic planning method.The particularity of traffic planning in the quantum secure communication network was analyzed,and a traffic planning model was given.Based on this model,the user wide area encrypted communication bandwidth could be planned in the case of determining the key distribution bandwidth of the backbone link.At the same time,the model could be used to adjust the bandwidth of key distribution in network bottleneck links and improve the network performance.Finally,the application of the proposed flow planning method was demonstrated by numerical simulation.